Low-profile, extremely wideband, dual-band-notched MIMO antenna for UWB applications. Issue 7 (19th March 2019) - Bhattacharya, Ankan; Roy, Bappadittya; Caldeirinha, Rafael F. S.; Bhattacharjee, Anup K.
Abstract: In this article, an extremely wideband, isolation-enhanced, low-profile "Multiple-Input-Multiple-Output" (MIMO) antenna along with dual-band-notched features has been investigated. The antenna proposed herein, possesses two mutually orthogonal staircase-etched radiators for achieving a wide bandwidth. The radiating elements are placed mutually perpendicular in order to achieve polarization diversity and high isolation, i.e. for minimization of mutual coupling effect between adjacent radiating elements. The antenna exhibits an extremely wide frequency bandwidth covering 1.2–19.4 GHz except two frequency band notches centered at 3.5 and 5.5 GHz, respectively, originated due to the incorporation of a "Rectangular Complementary Split Ring Resonator (RCSRR)" structure and by etching dual " L -shaped" slits in the ground plane. The center frequency of the notched bands is adjusted by fine tuning of the dimensions of the incorporated band-notching structures. Isolation level ( S 21 ) better than −20 dB has been obtained due to the insertion of a " T -shaped" parasitic element as a decoupling structure. A prototype of the proposed antenna having dimension of 20 mm × 20 mm (0.08 λ o × 0.08 λ o ) is fabricated and the antenna responses have been measured. Obtained results show that the miniaturized MIMO diversity antenna is undoubtedly a capable contender for communications supporting an extremely wide impedance bandwidth along with band-notched features for WLAN and WiMAX.